Feasibility of Ex Vivo Ligandomics - Prabuddha Waduge; Remya Ammassam Veettil; Bojun Zhang; Chengchi Huang; Hong Tian; Wei Li (Biomolecules)
We developed ligandomics for the in vivo profiling of vascular ligands in mice, discovering secretogranin III (Scg3) as a novel angiogenic factor that selectively binds to retinal vessels of diabetic but not healthy mice. This discovery led to the development of anti-Scg3 therapy for ocular vasculopathies. However, in vivo ligandomics requires intracardial perfusion to remove unbound phage clones, limiting its use to vascular endothelial cells (ECs). To extend ligandomics to non-vascular cells, we investigated ex vivo ligandomics. We isolated ECs and retinal ganglion cells (RGCs) from diabetic and healthy mouse retinas by immunopanning. We quantified the binding of clonal phages displaying Scg3 and vascular endothelial growth factor (VEGF), confirming that their binding patterns to isolated diabetic versus healthy ECs matched in vivo patterns. Additionally, Scg3 and VEGF binding to isolated RGCs reflected their in vivo activity. These results support the feasibility of ex vivo ligandomics. We further mapped ligands binding to immunopanned diabetic and healthy ECs and RGCs by ligandomics, confirming that Scg3 was enriched with selective binding to diabetic ECs but not healthy ECs or diabetic/healthy RGCs. These findings demonstrate the feasibility of ex vivo ligandomics, which can be broadly applied to various cell types, tissues, diseases, and species.